Sustainable and renewable energy from biomass wastes in palm oil industry: A case study in Malaysia - Wu, Qibai; Qiang, Thien Ching; Zeng, Guoxun; Zhang, Haiyan; Huang, Ye; Wang, Yaodong (International Journal of Hydrogen Energy, 2017)
Palm oil is one of the most important oils in the world and huge amounts of palm biomass wastes are generated through palm oil extracting process which could endanger the environment. Meanwhile, electricity shortage is getting worse due to lack of fossil fuel. To convert biomasses from palm oil industry for power generation is a beneficial approach for both power shortage and environmental degradation. In order to investigate and optimize the generation process of power and heat from the waste biomass in palm oil industry, an analytic study of a combined heat and power plant in a palm oil mill fuelled with sustainable and renewable biomass wastes was conducted using ECLIPSE software through a case study in Malaysia. The resources of the biomass wastes in the mill were identified and the samples were collected on site. The waste samples were analysed in laboratory and their calorific value, chemical composition and biomethane potential were found. A simulation model was then set up using ECLIPSE software and the model was validated using the practical data of the CHP plant. Three different combinations of the biomass wastes, including EFB and Shell as fuel for power generation, MF co-firing with Biogas, and power generation using KS, EFB and Biogas with preheaters, were used in the simulation. It was found that all of the three combinations were able to produce enough electrical power and heat (steam) to meet the power and heat demand for the production process. The simulation results indicated that the palm solid biomass wastes and the biogas produced by mill effluent were able to provide enough sustainable and renewable fuel for the palm oil production process; and it is possible to provide extra electricity for the nearby area, which is one of the best option for utilization of palm oil biomass wastes. Highlights > A feasibility study of a palm oil biomass CHP plant was conducted using ECLIPSE. > Three different combinations of biomass wastes were optimized through simulation. > It can produce enough electricity and heat (steam) for palm oil production demand. > It has great potential to provide electricity to the grid as well.
Keywords: Combined heat and power biomass wastes; Palm oil mill; Sustainable and renewable energy